Effect of Various Media on the Growth of Pleurotus ostreatus - Noor, Shireen (2016)
Cultivation of Pleurotus ostreatus (Oyster Mushroom) on different type of media substrate was being conducted in this study. The reason for this study is to determine the effectiveness of various types of media on the growth of P. ostreatus. Total of 13 media treatment were being tested on the growth of P. ostreatus. Three of the media used were based on the different concentration of Potato Dextrose Agar (PDA) which was full strength, half strength and quarter strength PDA respectively. Four of the treatments were based on agar type of media. One medium was prepared with agar only and another three were prepared with 10% milk, 10% coconut milk and 10% urea, respectively. Six type of organic waste media were tested along which were rice bran, coconut waste, coffee waste, tea waste, saw dust and combination of saw dust and rice bran. The growth of the mycelium over the media substrate was recorded daily by measuring the size of the mycelium growth in mm towards the edge and bottom of the container. Based on the 20 days daily observation, rice bran medium appeared to be the best treatment for organic substrate medium used while agar with coconut milk medium shows the best treatment for agar type of media used. The second, third and fourth best media for agar type of media are full strength PDA medium, half strength PDA medium and agar with milk medium respectively. On the hand, the second best media for organic substrate is tea waste medium, third best media is coconut waste medium and fourth best media for organic substrate media is saw dust medium. Coffee ground medium shows the least favourable media for growth of P. ostreatus as an organic substrate media while agar with urea show negative result in the growth of P. ostreatus as agar type of media due of the inappropriate concentration of urea used. Overall, rice bran medium show the best media for the growth of P. ostreatus by producing fruiting body on day 13 while agar and coconut milk medium is the second best media used by producing fruiting body on day 15 of the observation.